Adjuvant effects of medicinal herbs and probiotics for fish vaccines - Mehdi Soltani; Alan Lymbery; Seong Kyu Song; Pezhman Hosseini Shekarabi (Reviews in Aquaculture, 2019)
The most prominent limiting factor in aquaculture nowadays is infectious diseases as they lead to massive economic losses. These diseases are often partly controlled by vaccination, herbs or probiotics. Despite the fact that vaccination is the most effective prophylactic approach to disease prevention, researchers have started to use plant‐derived products and probiotics as adjuvants to boost the efficacy of fish vaccines. This review describes the efficacy and potency of plant extracts/essences and probiotics as adjuvants for various vaccines in aquaculture.